2013
DOI: 10.3382/ps.2012-02404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different magnesium sources on digesta and excreta moisture content and production performance in broiler chickens

Abstract: Reducing litter moisture is an effective measure to reduce the incidence of footpad dermatitis. Dietary mineral levels affect intestinal conditions with regard to osmolarity and water reabsorption. Magnesium is often used as a laxative, preventing reabsorption of water from the digesta, and as a consequence, more moisture in the excreta. The objective of the current experiment was to evaluate Mg in broiler diets as a model for reduced intestinal water reabsorption. Effects of magnesium source (magnesium sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
11
0
4
Order By: Relevance
“…Increased protein content of the digesta in the hindgut can, therefore, affect microbial composition in the hindgut and affect water reabsorption. However, in a previous experiment no relation of microbial composition and excreta moisture content was observed (van der Hoeven-Hangoor et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Increased protein content of the digesta in the hindgut can, therefore, affect microbial composition in the hindgut and affect water reabsorption. However, in a previous experiment no relation of microbial composition and excreta moisture content was observed (van der Hoeven-Hangoor et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, each sample was dried in a forced-air oven at 70°C for 24 h and weighed. Percent moisture was calculated using the following formula (Miles et al, 2011;van der Hoeven-Hangoor et al, 2013):…”
Section: Excreta Moisture Contentmentioning
confidence: 99%
“…Different with our results, Stockdale (2004) reported that adding 105 to 155 g MgSO 4 to the diet of cows during the last 3 weeks of gestation had a negative effect on intake before calving. Supplementation of MgSO 4 at doses of 0.255, 1.02, and 2.04 g/kg diet linearly reduced BW gain and feed intake in broiler chickens (Van der Hoeven-Hangoor et al, 2013). Stockdale (2004) interpretated that supplementation of MgSO 4 would seriously affect the palatability of the feed and reduce the feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding on finishing pig constipation with the addition of MgSO 4 to diets was reported by Tang (2000). According to Van der Hoeven-Hangoor et al (2013), adding Mg (MgSO 4 , MgO, and magnesium chloride (MgCl 2 ), each at 3 levels (0.255, 1.02, and 2.04 g/kg diet)) to the diet of broilers linearly increased the excreta moisture content, following the pattern MgCl 2 >MgSO 4 = MgO, which has confirmed that Mg can prevent reabsorption of water from the digesta, and as a consequence, more moisture will be present in the excreta.…”
Section: Discussionmentioning
confidence: 99%